História, literatura e cinema: um debate sobre a historicidade das imagens dos piratas e da pirataria - Barcelos, Ivana Borges (2016)
We seek, through this work, to understand the construction of the pirates’ images from the Golden Age of Piracy (late seventeenth through early eighteenth century) through the observation of the circulation of these images, which are not limited to one field of knowledge. We take into account the importance of the book “A General History of the robberies and murders of the most notorious pirates...” written by Charles Johnson for these constructions, not only literary, but also historiographical provided that the stories of pirates and piracy gained ground in historiography from the twentieth century on. We also seek to show that this historiographical space arises opposed to an apparent historiographical silence about these stories that lasts for about two centuries, related to a new way of writing history in the aesthetic regime, where it arises as a science through a poetics of knowledge, of which the philosopher Jacques Rancière helps us reflect. Lastly, reflecting upon how these images of pirates circulate nowadays, we seek to understand the historicity of the pirates’ images within that aesthetic regime based on some scenes of the film series Pirates of the Caribbean by Disney™.